2022
DOI: 10.5964/ejop.2051
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between problematic internet use, WhatsApp and personality

Abstract: The manner and frequency of Internet use may reflect the needs, preferences, values, personal motivations and personality characteristics of users. The aim of this research was to analyse the relationship between the Big Five Personality factors and impulsivity with Problematic Internet Use and the Negative Impact of WhatsApp. The sample consisted of 630 university students (75.7% female) aged between 18 and 62 years (M = 21.23). The results indicated that the Big Five Personality factors and impulsivity corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In a study that involved 630 university students, of whom 75% were females, it was reported that those with impulsive personalities were at higher risk of developing problematic internet use when utilizing WhatsApp. 19 Nevertheless, evidence concerning the potential impact of its use on mental wellbeing in clinical settings is presently lacking. Although the existing medical literature seems inclined to promote its use in these settings, the consequences on the mental health of workers is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…In a study that involved 630 university students, of whom 75% were females, it was reported that those with impulsive personalities were at higher risk of developing problematic internet use when utilizing WhatsApp. 19 Nevertheless, evidence concerning the potential impact of its use on mental wellbeing in clinical settings is presently lacking. Although the existing medical literature seems inclined to promote its use in these settings, the consequences on the mental health of workers is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Problematic internet use can signi cantly impact an individual's physical, mental, and social well-being, posing a threat to the general welfare of society (11,12). Therefore, it is crucial for public health policies and treatment approaches to address this issue.…”
Section: Introductionmentioning
confidence: 99%
“…According to a biopsychosocial model of addiction [ 8 ], the development of internet addiction may involve contributions from neurobiological (e.g., genetics and neurotransmitters) [ 9 , 10 ], more stable psychological (e.g., personality features, impulsivity, inhibitory-control tendencies) [ 11 , 12 , 13 ], or more state-related psychological (e.g., stress, loneliness) factors [ 14 , 15 ], as well as factors related to social environment (e.g., social norms, family, school) [ 16 , 17 ]. Of these, personality tendencies have received considerable attention, in that they may influence risk for internet addiction [ 18 , 19 ]. Among the personality factors, extraversion and its opposite, introversion, are considered important [ 20 ].…”
Section: Introductionmentioning
confidence: 99%